Results of the bat survey in the Dong Phuc, Ban Thi - Xuan Lac areas (Bac Can province) and the Sinh Long, Ban Lam areas (Tuyen Quang province) - Son, Nguyen Truong; Thong, Vu Dinh (Academia Journal of Biology, 2015)
Results of the bat survey in the Dong Phuc, Ban Thi - Xuan Lac areas (Bac Can province) and the Sinh Long, Ban Lam areas (Tuyen Quang province)